Adsorption of Individual and Mixtures of β‐Blockers and Copper in Soils and Sediments. (26th September 2022) - Smith, Rose‐Michelle; Sayen, Stéphanie; Guillon, Emmanuel
Abstract: The (bio)availability of pharmaceuticals at solid/water interfaces is governed by their sorption, which determines their concentrations in groundwaters and surface waters in contact with biota, and can be affected by the presence of other contaminants such as metallic trace elements likely to compete for adsorption sites and form complexes with pharmaceuticals. We studied the adsorption of the pharmaceuticals propranolol and sotalol—two β‐blockers—on one soil and one sediment using batch experiments to assess their (bio)availability. The influence of contact time, pH, and concentration was studied. As in the real environment these contaminants are not alone but in mixtures, and they were studied alone, simultaneously added, and in the presence of Cu 2+, which is known to form coordination complexes with propranolol and sotalol, but their presence in mixtures did not alter their adsorption properties. Sotalol was more mobile in water and thus more bioavailable for organisms than propranolol. The mobility in surface waters of both β‐blockers and thus their bioavailabity for organisms is more important than their risk of transfer to groundwater during rainwater infiltration and to surface water due to runoff. Environ Toxicol Chem 2022;41:2700–2707. © 2022 The Authors. Environmental Toxicology and Chemistry published by Wiley Periodicals LLC on behalf of SETAC.